Correction: Self-template synthesis of hierarchical CoMoS3 nanotubes constructed of ultrathin nanosheets for robust water electrolysis. Issue 25 (19th June 2017) - Guo, Jinxue; Zhang, Xinqun; Sun, Yanfang; Tang, Lin; Zhang, Xiao
Abstract : Correction for 'Self-template synthesis of hierarchical CoMoS3 nanotubes constructed of ultrathin nanosheets for robust water electrolysis' by Jinxue Guo et al., J. Mater. Chem. A, 2017, DOI: ; Web:10.1039/c7ta02768k .